Constantes del mundo literario de Juan Marsé - Dóra Faix (Mélanges de la Casa de Velázquez, 2024)
This article analyses the most characteristic elements of Juan Marsé’s literary world by examining the author’s different novels. The basis of the analysis is the immanence of the work, that is to say, the texts themselves. First of all, the narrative space of post-war Barcelona is described, since from the author’s first novel, Encerrados con un solo juguete, this element constitutes one of the bases of the narrative. Next, we analyse from a narratological point of view the aventis (stories told by certain characters in the work), which not only form part of the plot, but also have symbolic value and, above all, determine the narratological structure of the work. Although they are present in several novels, the aventis create a more complex scheme, especially in Si te dicen que caí, where the limits between the different levels of the narrative disappear. Finally, the reminiscences in the texts of the writer himself are analysed to see whether he really intends to offer us an image of himself or to transmit the collective memory of a whole generation.